Information Content of Share Buybacks from an Earnings Perspective = (Kandungan Maklumat Pembelian Semula Saham dari Perspektif Pendapatan) - Chin, Chee Ling; Mohamad, Jais; Salawati, Sahari; Chin, Chee Hua (Penerbit UKM, Universiti Kebangsaan Malaysia., 2023)
This study aims to examine the predictive ability of share buybacks from an earnings perspective. Panel data regression analysis is conducted to determine the impact of share repurchases on future firm performance using Malaysian publicly listed companies data over 2000-2020. This study is significant because of the importance of share buybacks to attract investors, especially during crisis periods. The results show that the share repurchase ratio is positively and significantly related to all the proxies for future firm performance, as represented by return on assets, return on equity, operating income, and funds from operations that are all measured in the following year of share buyback. The validity of the result is confirmed when tested with an alternative explanatory variable, while the sensitivity test shows that the signaling power of share repurchase is more apparent among share-repurchasing firms with small market capitalization. Overall, the findings support the information signaling hypothesis and suggest that share buybacks in Malaysia provide useful information about a company’s earnings prospects.